Exploring the relationships between tradeoffs and synergies among island ecosystem service bundles: a study on Zhoushan archipelago located on the Southeast Coast of China - Xiao, Yang; Zhang, Huan; Ma, Ke; Perera, Hadinnapola Appuhamilage Chintha Crishanthi; Ramli, Muhammad Zahir; Deng, Yuncheng (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Due to the rapid rise of China’s coastal economic zone, the urbanization of the surrounding islands has accelerated. Intensive disturbance caused by human activities and frequent changes in land types have resulted in the continuous erosion of ecological sources and the degradation of ecosystem services on the islands year by year. It is particularly important to explore sustainable development strategies for the islands to achieve a balance between conservation and development, which is particularly important for the islands in the process of urbanization. Taking Zhoushan Archipelago as an example, this paper uses multi-source spatial data and employs In VEST models and USLE to quantify island ecosystem services. Furthermore, using principal component analysis and cluster analysis, the study aims to identify clusters of island ecosystem services and investigate their tradeoffs, synergistic mechanisms, and regional heterogeneity using spatial analysis. In addition to providing island urban planners with effective zoning governance recommendations and assistance in spatial planning to promote coordinated and sustainable development, the findings of this study can assist in the development of appropriate management plans for each ecological functional service cluster on islands.